Removal of H2S from Synthetic Waste Gas Streams Using a Biotrickling Filter (Iranian Journal of Chemical Engineering)
The removal of hydrogen sulfide (H2S) from airstreams was studied in a biotrickling filter packed with porous lava as a carrier of Thiobacillus thioparus (DSM5368) with counter current flows of the air and liquid streams. The effect of operating parameters on biotrickling filter performance was studied. Experiments were performed at different empty bed residence times (9-60 sec), and moderate H2S concentrations (10-90 ppm) to assess the performance of biotrickling filter at different conditions of these parameters. The effect of superficial liquid velocity (0.98-1.95mh-1) on the performance of biotrickling filter was evaluated. Increasing superficial liquid velocity decreased removal efficiency of the BTF. The gradual change in the concentration of H2S in different heights of the BTF was investigated. Decreasing empty bed residence time lead to a slight increase in the homogeneity of the removal at different heights of the BTF; however the effect of change in the inlet concentration was insignificant. Complete removal was achieved in the first 85% of the bed. To gain a brief insight into the robustness of the biotrickling filter, its performance was investigated after several upsets in the system.